2010
DOI: 10.1007/s00192-010-1252-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment choice, duration, and cost in patients with interstitial cystitis and painful bladder syndrome

Abstract: Introduction and hypothesisIn order to better understand provider treatment patterns for interstitial cystitis (IC)/painful bladder syndrome, we sought to document the therapies utilized and their associated expenditures using a national dataset.MethodsA cohort was created by applying the ICD-9 diagnosis of IC (595.1) to INGENIX claims for the year 1999. Subjects were followed for 5 years, and patterns of care and related expenditures were evaluated.ResultsOf 553,910 adults insured in 1999, 89 subjects had a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 22 publications
0
37
1
Order By: Relevance
“…We hypothesize that PPS treatment likely led to a significant reduction in pain of the MPS animals, contributing to the increased motility. A reduction in pain also is the most prominent change in IC patients treated with PPS [10], [21]. There also were clear changes in the articular chondrocytes that suggested improved articular joint function, which together with improvements in bone morphology and spine biomechanics might be partly responsible as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We hypothesize that PPS treatment likely led to a significant reduction in pain of the MPS animals, contributing to the increased motility. A reduction in pain also is the most prominent change in IC patients treated with PPS [10], [21]. There also were clear changes in the articular chondrocytes that suggested improved articular joint function, which together with improvements in bone morphology and spine biomechanics might be partly responsible as well.…”
Section: Discussionmentioning
confidence: 91%
“…Pentosan polysulfate (PPS) is an FDA-approved, oral medication (Elmiron®) with potent anti-inflammatory effects that is used to treat patients with interstitial cystitis (IC) [10]. It also has been shown to promote chondrogenesis in animals with osteoarthritis (OA) [11][13], and has been used off-label to treat OA patients [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Berry and co-authors report the prevalence of IC/BPS at between 3 and 8 million women in the United States [3]. Few patients achieve long-term remission of symptoms despite a range of treatments [1,33]. A substantial body of research has explored bladder pathology and other peripheral tissue abnormalities, however, a large number of IC/BPS patients lack any discernible end organ inflammation, and do not respond to treatment of peripheral tissues (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…149 A 2011 study found the U.S. direct costs of IC to be $22 billion. 150 Chronic Headache (Migraine and Tension-Type) Both migraine and tensiontype headaches are defined as primary headache disorders, i.e., those that exist independent of another disorder. These headache disorders are classified as chronic when they occur 15 days or more a month for three months in the absence of medication use (migraine) 161 or for six months (chronic tension-type).…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%